The Effectiveness Of health Education Using leaflets On Increasing Knowledge And Hemoglobin Levels In Pregnant Women At The Independent Practice Of Midwife Salabiah, Banda Sakti District, Lhokseumawe City, in 2025 - Lina Ekawati; Mawarni Yunita; Mutiana Mutiana; Cut Susandari; Khairaturrahmi Khairaturrahmi (CV. AFDIFAL MAJU BERKAH, 2026)
Anemia remains a global health problem, particularly among pregnant women. In Aceh, the prevalence reached 36.3% in 2024, while in Lhokseumawe City in 2025, there were 154 cases out of 4,253 pregnant women (3.62%), with a higher rate at BPM Bidan Salabiah (25.9%). A preliminary survey in August 2025 showed 35% of pregnant women had hemoglobin levels <11 g/dL along with low understanding of nutrition and iron supplementation. This study aimed to determine the effectiveness of health education using leaflets on pregnant women’s knowledge about hemoglobin levels at BPM Bidan Salabiah, Banda Sakti District, Lhokseumawe City. The research was conducted on August 20, 202. The study employed a quasi-experimental one group pre-test post-test design with 7 purposively selected respondents. Data were collected using a knowledge questionnaire and analyzed with the paired t-test. Results showed the average knowledge score before the intervention was 4.86 and increased to 8.29 after, with a mean difference of 3.24. Statistical analysis revealed a p-value of 0.001 (<0.05), indicating a significant effect of leaflet-based health education on knowledge improvement. In coclusion, leaflets are effective in increasing pregnant women’s knowledge about hemoglobin levels as an effort to prevent anemia. It is recommended that health workers, particularly midwives, use leaflets as a simple, practical educational tool. Future studies should involve larger samples and consider additional variables such as adherence to iron tablet consumption and actual hemoglobin levels.